Difficulties in Writing Scientific Papers and Journal Publications: English Lecturers’ Perspective from Various Higher Institutions in Indonesia - Fitria, Tira Nur (Udayana Journal of Social Sciences and Humanities; Vol 8 No 2 (2024): Vol 8 No 2 (2024): UJoSSH, September2024DO - 10.24843/UJoSSH.2024.v08.i02.p04, 2024)
Abstract This research describes English lecturers’ difficulties in writing scientific articles and journal publications. This research is descriptive qualitative. The analysis shows that lecturers’ difficulties in writing scientific articles are related to psychological factors including mood, physical condition, concentration, workplace and living environment, limited writing time, and lack/no support system in writing. The other difficulties are related to cognitive factors including various types of research, research interests, research article topics, research title, research background, research gaps/novelties, previous studies in certain years, theories/references in national and international journals, theories/references in nationally and internationally published books, writing and developing writing, paraphrasing, citations, and references with the reference manager, type of research method, appropriate data collection methods, specified data collection methods, data analysis, writing results/findings, discussion, conclusions, and suggestions. The other cognitive factors including the systematics/structure of scientific articles (author guidelines), appropriate previous studies, suggestions, and an abstract are not the lecturers’ difficulties in writing scientific articles. While, lecturers’ difficulties in writing scientific articles are not related to linguistic factors including grammar, tenses, spelling, diction, and punctuation. Lecturers’ difficulties with the publications related to the appropriate journal, journal accreditation, research focus, specific scope, submission deadline, the edition of certain publications, and publication costs. Lecturers agree that institutions hold training on writing scientific articles and publications in journals, support lecturers in writing scientific articles and publications, and support lecturers to publish scientific articles by providing funding for publication costs, give awards to lecturers who actively write scientific articles and publish them in national/international journals.